(untitled) - Holger Hovgard (Rome, 2000)
This manual defines methods for estimating selectivity of gillnet and longline gears, with particular reference to the use of these gears in abundance surveys. The manual covers how to gear design, the basic concepts of size selection and fish morphometric data might be used detail and examples given of their application in speadsheets.
Keywords: fisheries